2018
DOI: 10.1155/2018/6762146
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor Yellow A Promoted Bone Mineralization and Inhibited Bone Resorption Which Reversed Glucocorticoids-Induced Osteoporosis

Abstract: Glucocorticoids intake is the most common cause of secondary osteoporosis. Clinical studies have shown that 50% patients develop glucocorticoids-induced osteoporosis (GCIOP) after taking glucocorticoids for more than 6 months. Hydroxysafflor yellow A (HYA) is one main active ingredient in Carthamus tinctorius L. Previous studies have shown that HYA promoted bone marrow mesenchymal stem cells to differentiate into osteoblasts which promoted bone formation. Therefore, we speculated that HYA has a therapeutic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…The results showed that HSYA exhibited a remarkable protective effect on OVX-induced osteoporosis in a rat model as confirmed by micro-CT and histological and immune-histochemical analysis. This finding is consistent with the previous report that HSYA could inhibit bone resorption and reverse glucocorticoid induced bone loss in zebrafish [38].…”
Section: Discussionsupporting
confidence: 94%
“…The results showed that HSYA exhibited a remarkable protective effect on OVX-induced osteoporosis in a rat model as confirmed by micro-CT and histological and immune-histochemical analysis. This finding is consistent with the previous report that HSYA could inhibit bone resorption and reverse glucocorticoid induced bone loss in zebrafish [38].…”
Section: Discussionsupporting
confidence: 94%
“…For example, some of the genera that increased in abundance with the HLA diet are known short chain fatty acid producers including Akkermansia, Butyricimonas, Coprococcus and members of the Clostridiales order. Abundance of Akkermansia and especially the species Akkermansia muciniphila abundance has previously been linked to dietary fat intake, although this relationship is complex, with both increased and decreased abundance has been reported depending on the type of lipid, the overall composition of the diet or the presence of additional treatments (22,24,31,34). In general however, Akkermansia abundance is negatively correlated with dietary fat intake (30).…”
Section: Discussionmentioning
confidence: 99%
“…The injection of HSYA at different concentrations (0.1, 1.0, and 10.0 μM) prevented bone mineralization, osteoblasts viability, and inhibited bone resorption. In vivo, the effect of HSYA on bone formation and glucocorticoids-induced osteoporosis (GCIOP) was demonstrated using zebrafish [ 90 ]. The effects of crude extract of safflower seed were examined on osteoblast differentiation and intracellular calcium ion concentration in MC3T3-E1 cells, showing the ability to prevent osteoporosis and protect against bone loss [ 91 ].…”
Section: Safflower Pharmacological Activitymentioning
confidence: 99%